OPEN DUCTUS ARTERIOSUS IN PREMATURE INFANTS WITH EXTREMELY LOW AND VERY LOW BODY WEIGHT - Игишева, Людмила Николаевна; Звягина, Жанна Анатольевна; Цой, Елена Глебовна; Шабалдин, Андрей Владимирович; Вакулова, Тамара Михайловна (Mother and Baby in Kuzbass, 2025)
The aim of the research – to identify significant factors affecting the postnatal functioning of PDA in premature infants with extremely low and very low body weight and to evaluate them from a manageability perspective. Materials and methods. In a continuous prospective study, 98 premature infants in the first 72 hours of life were divided into 2 groups according to the results of an echocardiological examination (67 children with PDA, 31 children without DA At the age of 1 month of life, 90 newborns were monitored, 48 children had open AP, and 42 children had no AP. Hemodynamic and laboratory data (NT- proBNP) were studied. Results. At 72 hours of life, premature infants with PDA and without it had no hemodynamic differences. At 1 month of life, the features of intracardiac hemodynamics were revealed in the PDA group: myocardial hypertrophy (thickness interventricular septum 3.26 mm, p = 0.039), dilation of the left ventricle (end systolic volume 1.97 ml, p = 0.04), tricuspid regurgitation (21.29 mmHg, p = 0.021). The level of NT – proBNP in the early neonatal period and at 1 month of life did not exceed the accepted reference values. At 1 month, a significant set of factors was determined: the duration of the anhydrous period, the Apgar score at 5 minutes, the syndrome of general depression of the central nervous system at 2 weeks of life, respiratory acidosis at birth, hemodynamic parameters at 72 hours of life (large final diastolic size and open oval window), changes in the pulmonary interstitium at 2 weeks of life, based on which, using multiple logistic regression, an algorithm for the probability of PDA is constructed. Controlled and controllable factors of the state of the AP can be recognized as the parameters of the acid-base state. Conclusion. Signs of myocardial remodeling were diagnosed as a result of adaptive processes in the body of premature infants. Assessment and correction of the acid-base state parameters (BE, pO2 and pCO2) in the first 72 hours of postnatal life will allow monitoring of PDA.